Ursolic acid induces apoptosis and disrupts host-parasite interactions in Theileria annulata-infected cells - Sakshi Singh; Madhusmita Subudhi; Vengatachala Moorthy A; Akash Suresh; Paresh Sharma (International Journal for Parasitology: Drugs and Drug Resistance)
This study explores the anti-proliferative and anti-parasitic properties of ursolic acid (UA) in Theileria annulata-infected bovine (TA) cells. Dose-response analyses determined an IC50 value of approximately 5 μg/mL for UA, demonstrating selective cytotoxicity toward infected cells with minimal impact on healthy cells. UA treatment induced pronounced morphological alterations and apoptosis in TA cells, as evidenced by light microscopy and a time-dependent increase in cell mortality. Notably, UA exhibited consistent efficacy against both buparvaquone (BPQ)-sensitive and BPQ-resistant TA cell lines, highlighting its broad-spectrum anti-parasitic potential. Mechanistic investigations revealed that UA triggers DNA damage, elevates reactive oxygen species (ROS) levels, disrupts mitochondrial function, and induces sub-G1 phase arrest, culminating in apoptosis primarily via the intrinsic pathway. Mass spectrometry-based proteomic profiling identified significant perturbations in host cell pathways, including DNA repair mechanisms, cell cycle regulation, and signaling networks, alongside direct interference with parasite metabolic processes. Western blot analysis further confirmed UA-mediated modulation of host cell signaling pathways and chromatin organization. Given the rising incidence of drug-resistant T. annulata strains, the development of novel therapeutic strategies is imperative. These findings highlight UA's multifaceted mechanism of action, targeting both parasitic and host cellular processes, and position it as a promising candidate for the treatment of bovine theileriosis.